A Continuum of Play-Based Learning: The Role of the Teacher in Play-Based Pedagogy and the Fear of Hijacking Play. Issue 3 (3rd April 2017) - Pyle, Angela; Danniels, Erica
ABSTRACT: Research Findings : Research has demonstrated the developmental and educational benefits of play. Despite these benefits, teacher-directed academic instruction is prominent in kindergarten. There is increasing acknowledgment in curricula and policies of the challenges presented by a lack of play in classrooms and the need to support academic learning using developmentally appropriate practices. Current research emphasizes a narrow definition of play-based learning as a child-directed practice, resulting in teacher uncertainty about the implementation of this pedagogical approach. Fifteen kindergarten classrooms were examined using qualitative methodology, including observations and teacher interviews. Two different teacher profiles emerged: The 1st profile saw play and learning as separate constructs and reported challenges meeting academic demands using play-based learning. Their students primarily engaged in free play. The 2nd profile believed that play could support academic learning and that teachers fill an important role in play. Their students engaged in 5 different types of play, situated along a continuum from child directed to more teacher directed. Practice or Policy : The continuum of play-based learning provides a broader and more concrete definition of play-based learning to help teachers implement this pedagogical approach and to enhance the study of play-based learning in early years research.